Statistical Approach for Modeling of Daily Global Solar Radiation on Horizontal Surfaces Over Hebron City, Palestine - Alsamamra, Husain (Journal of Technology Innovations in Renewable Energy, 2013)
Understanding solar radiation data is essential for modeling solar energy systems because it is non-polluting, non-depletable, reliable, and pollution free. Four-years measured average daily global solar radiation data on horizontal surfaces at Hebron city in Palestine were used for the model assessment. Statistical results showed that all four suggested models can accurately predict the solar irradiance of a 31° 57’ N (latitude angle of Hebron) on a horizontal oriented surface, indicating the good predictive ability for modeling a horizontal surface. The obtained models have a high value of regression coefficient and give best fit through the measured values. This work illustrates also the use of mathematical formula to develop a predictive model for the duration of sunshine using measured solar radiation data for Hebron city. The present work showed that the predicted results were in good agreement with the observed data, and the expected solar radiation behavior.